Alpha keeps it together: Alpha oscillatory synchrony underlies working memory maintenance in young children - Sato, Julie (Dev Cogn Neurosci, 2018)
Working Memory (WM) supports a wide range of cognitive functions, and is positively associated with academic achievement. Although fMRI studies have revealed WM networks in adults, little is known about how these networks develop to support successful WM performance in children. Using magnetoencephalography, we examined the networks underlying the maintenance of visual information in 6-year-old children. We observed an increase in mean whole-brain connectivity that was specific to the alpha frequency band during the retention interval associated with correct compared to incorrect responses. Additionally, our network analysis revealed elevated alpha synchronization during WM maintenance in a distributed network of frontal, parietal and temporal regions. Central hubs in the network were lateralized to the left hemisphere with dominant fronto-temporal connections, including the dorsolateral prefrontal cortex, middle temporal and superior temporal gyri, as well as other canonical language areas. Local changes in power were also analysed for seeds of interest, including the left inferior parietal lobe, which revealed an increase in alpha power after stimulus onset that was sustained throughout the retention period of WM. Our results therefore implicate sustained fronto-temporal alpha synchrony during the retention interval with subsequent successful WM responses in children, which may be aided by subvocal rehearsal strategies.